Descripción de la encuadernación del libro de los muertos de la Guerra Civil Española - Francisco Olmos, José María de; Carpallo Bautista, Antonio (Revista General de Información y Documentación, 2006)
It may be sad to see that one of the best bindings carried out in Spain holds the booking record of about 22.000 people of the Spanish Civil War buried in the Basilica of the Valley of the Fallen. In this short paper the binding is thoroughly described paying close attention to the materials and techniques employed, the decoration that is displayed on the covers, endpapers spines and cuttings, and even the elements of protection of the binding such as the shirt or cover and the case. It is analysed the state of conservation of this work that at present is kept in the Library of the Royal Palace.
Keywords: Documentary analysis of bindings; Library of the Royal Palace (Madrid); Basilica of the Valley of the Fallen (Madrid); Francisco Franco Bahamonde; Spanish Civil War; Vicente Cogollor Mingo; Ramón Mimendi Diego; Luis Moreno Martín